A presença da narrativa transmídia no jornalismo regional: análise das experiências dos jornais Folha de Londrina e O Povo - Souza, Sebastião José Nascimento de (2023)
This study starts from the hypothesis that the transmedia journalistic narrative has evolved, as an important resource for the user and to bring him closer to regional narratives. Based on the experiences of the newspaper Folha de Londrina, from Paraná, and the newspaper O Povo, from Ceará, this research or how the objective of transmedia narrative in regional journalism is characterized, through a qualitative, exploratory and inductive research, through the Content Analysis Method (AD). To this end, narratives were traced with three specific objectives: to characterize transmedia in transmedia; to propose elements of transmedia journalism; understand how the transmedia narrative is configured as an agent of reinvigoration of regions and places. Thus, research journalism, studies on journalistic convergence, transmedia and regional journalism stand out. A proposal of five transmedia journalism was carried out, namely: multiplatform, integrated multimedia, user participation, interactive and drawn designer. This study concludes that regional themes are being reinvigorated from the transmedia narrative type and that this narrative is used in regional journalism to intensify amid so many categories in journalism. Folha de Londrina, of the five proposed elements, presents all the principles; however, the multiplatform principle is presented in a limited way in the transmedia specials analyzed. The journalistic element O Povo not only presents the multiplatform journalistic principle and explores the narrative pattern in a strategic way, O Povo does not only present the multiplatform principle strategically.